The Construction of a Replica Section of the Middle Subneolithic Purkajasuo Lath Screen Fish Weir at Kierikki Stone Age Centre, Finland - Peter Groom (EXARC, 2018)
In July 2018 the Mesolithic Resource Group attended the Kierikki Stone Age Centre, Pahkalantie, Finland. The visit provided us with the opportunity to practice experimental archaeology in a ‘Stone Age’ landscape at Kierikki. One project was the reconstruction of a section of the Neolithic wooden fish weir from the site of Purkajasuo, which is on display in the museum. Constructed of pine, willow and birch bark, the section demonstrates the creative use of materials local to the area. We employed an actualistic approach, using technologies and materials available to the inhabitants of the area between 3300-2900BC. Our work demonstrated the effective use of resources by Stone Age societies and reinforced the importance and effectiveness of simple tools. For most of the project we used unmodified tools.